Development of Multimedia Google sites for Ehancing Conceptual Understanding and Students Motivation in Digestive System Topic - Wardatul Hakimah; Dian Nugraheni; Habiddin; Yayuk Mulyati; Erti Hamimi (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
This research is based on the limited use of learning media which results in students experiencing difficulties in understanding lessons and a lack of learning motivation, which impacts low learning outcomes. This research aims to develop valid, effective, and practical google sites multimedia to improve conceptual understanding and student motivation in the material of the digestive system. The research method used was research and development (R&D) with the ADDIE model, namely: analyze, design, development, implementation, evaluation. Data were collected through observation, interviews, and questionnaires. Validation by material experts showed a